Determination of variable region sequences from hybridoma immunoglobulins that target Mycobacterium tuberculosis virulence factors. - Hui-Chen Chang Foreman (Public Library of Science (PLoS), 2021)
Mycobacterium tuberculosis (Mtb) infects one-quarter of the world's population. Mtb and HIV coinfections enhance the comorbidity of tuberculosis (TB) and AIDS, accounting for one-third of all AIDS-associated mortalities. Humoral antibody to Mtb correlates with TB susceptibility, and engineering of Mtb antibodies may lead to new diagnostics and therapeutics. The characterization and validation of functional immunoglobulin (Ig) variable chain (IgV) sequences provide a necessary first step towards developing therapeutic antibodies against pathogens. The virulence-associated Mtb antigens SodA (Superoxide Dismutase), KatG (Catalase), PhoS1/PstS1 (regulatory factor), and GroES (heat shock protein) are potential therapeutic targets but lacked IgV sequence characterization. Putative IgV sequences were identified from the mRNA of hybridomas targeting these antigens and isotype-switched into a common immunoglobulin fragment crystallizable region (Fc region) backbone, subclass IgG2aκ. Antibodies were validated by demonstrating recombinant Ig assembly and secretion, followed by the determination of antigen-binding specificity using ELISA and immunoblot assay.